2023
DOI: 10.1111/jcpp.13790
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding duration is associated with larger cortical gray matter volumes in children from the ABCD study

Abstract: Background Despite the numerous studies in favor of breastfeeding for its benefits in cognition and mental health, the long‐term effects of breastfeeding on brain structure are still largely unknown. Our main objective was to study the relationship between breastfeeding duration and cerebral gray matter volumes. We also explored the potential mediatory role of brain volumes on behavior. Methods We analyzed 7,860 magnetic resonance images of children 9–11 years of age from the Adolescent Brain Cognitive Develop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 78 publications
1
3
1
Order By: Relevance
“…Unlike cow’s milk or most formula feeds, breast milk contains large amounts of long-chain polyunsaturated fatty acids, especially docosahexaenoic acid (DHA), an essential constituent of cell membranes in the central nervous system. Our observation concurs with previous findings that positively correlate breastfeeding with larger grey matter volume and thus potentially contribute towards better mental health and cognitive function 54 , 55 .…”
Section: Discussionsupporting
confidence: 93%
“…Unlike cow’s milk or most formula feeds, breast milk contains large amounts of long-chain polyunsaturated fatty acids, especially docosahexaenoic acid (DHA), an essential constituent of cell membranes in the central nervous system. Our observation concurs with previous findings that positively correlate breastfeeding with larger grey matter volume and thus potentially contribute towards better mental health and cognitive function 54 , 55 .…”
Section: Discussionsupporting
confidence: 93%
“…7 Notably, a recent study using the ABCD data showed that longer breastfeeding duration is associated with larger global and regional cortical GM volumes, which in turn impact impulsivity personality and behavioral problems. 3 Distinct from prior studies, we saw most robust findings in the cortical SA associated with breastfeeding duration. Taking this together with known relationships between cortical SA and adiposity markers, it further corroborates the multifaceted impact of breastfeeding on development.…”
Section: Discussioncontrasting
confidence: 71%
“…These results are in line with prior studies showing positive relationship between breastfeeding duration in infancy and global brain measures years later. 2,3,8 A binary categorization for breastfeeding (>0 months breastfeeding vs. 0 months breastfeeding) yielded similar but less significant effects because data distribution within the breastfeeding categories was skewed towards the 1-6 months duration. Our results indicate that increases in the breastfeeding duration are associated with increases in cortical SA, cortical and subcortical GM volume at 9-10 years.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations